2023
DOI: 10.1038/s41514-023-00105-5
|View full text |Cite
|
Sign up to set email alerts
|

Recent insights into the crosstalk between senescent cells and CD8 T lymphocytes

Abstract: Recent reports in oncological and non-oncological experimental setups provide strong evidence that senescent cells are under the surveillance of CD8 T cell-mediated adaptive immunity. These new data also shed light on the mechanisms that sensitize senescent cells to CD8 T cell-dependent killing, as well as those that enable senescent cells to evade CD8 T cell immunosurveillance. Understanding the interplay between cellular senescence and the adaptive immune system may open new strategies to ameliorate aging an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In this regard, a recent unbiased proteomic approach revealed that PD‐L2, but not PD‐L1, is upregulated in tumor cells after therapy‐induced damage and cellular senescence [298]. Furthermore, specific blockade of PD‐L2 could improve chemotherapy efficacy by reducing the intratumoral burden of senescent cells and the associated recruitment of immunosuppressive cells [298–300]. In our hands, the FASTIS state was accompanied by the transcriptional activation of PD‐L1 but not of PD‐L2 (unpublished observations).…”
Section: Fasn: a Multi‐faceted Regulator Of Immune Resistancementioning
confidence: 60%
“…In this regard, a recent unbiased proteomic approach revealed that PD‐L2, but not PD‐L1, is upregulated in tumor cells after therapy‐induced damage and cellular senescence [298]. Furthermore, specific blockade of PD‐L2 could improve chemotherapy efficacy by reducing the intratumoral burden of senescent cells and the associated recruitment of immunosuppressive cells [298–300]. In our hands, the FASTIS state was accompanied by the transcriptional activation of PD‐L1 but not of PD‐L2 (unpublished observations).…”
Section: Fasn: a Multi‐faceted Regulator Of Immune Resistancementioning
confidence: 60%
“…However, the impact of senescent cells on tumor immune microenvironment remains incompletely understood [ 55 ]. Senescent tumor cells contribute to adjuvanticity and antigenicity but also trigger immune checkpoint expression, heterogeneously affecting innate and adaptive immunity [ 56 , 57 ]. In our study, we aimed to explore the potential role of neutrophils in this context, addressing their recruitment and activation by senescent tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Using senescence immune surveillance, senescent cells are naturally removed by the body’s own immune cells such as macrophages, T-cells, natural killer cells (NK cells) ( 72 ) and microglia in the brain ( 73 , 74 ). However, due to age-related immunosenescence and the capability of senescent cells to evade immune surveillance, senescent cells are spared and accumulate in diverse tissues ( 75 ).…”
Section: Cellular Senescencementioning
confidence: 99%